PENGARUH MOTIVASI, LINGKUNGAN KERJA DAN PENGEMBANGAN KARIER TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI INTERVENING PADA SMK DI KABUPATEN SEMARANG - Yudho Purnomo (E-logis : Jurnal Ekonomi Logistik, 2020)
Employee performance is real behavior that appears each employee as the resulting performance in accordance with its role within the company. Usually people who are referred to as the high performance levels of productive people, and conversely those whose levels do not reach the standard, said to be nonproductive or low performance. High and low performance information an employee can not be obtained for granted, but obtained through a long process that employee appraisal process. Many factors can affect the employees performance, such as motivation, work environment, career development and job satisfaction. The purpose of this study was to analyze the influence of motivation, work environment and career development on employee performance and job satisfaction as an intervening. Population and sample in this research is the teachers and staff of vocational schools in Semarang regency totaling 101 people. Selected samples were 50 teachers. This type of data is primary data. Data collection method was questionnaire. Data analysis technique used is path analysis. The results showed that: Motivation proved positive and significant effect on job satisfaction. Work environment proved positive and significant effect on job satisfaction. Career development proved positive and significant effect on job satisfaction. Motivation proved positive and significant effect on employee performance. Work environment proved positive and significant effect on employee performance. Career development proved positive and significant effect on employee performance. Job satisfaction proved positive and significant effect on employee performance. Motivation proved effect on the performance of employees through job satisfaction as an intervening variable. Work environment proved effect on the performance of employees through job satisfaction as an intervening variable. Career development proved effect on the performance of employees through job satisfaction as an intervening variable